BY MEANS OF LINDEBERG’S CENTRAL LIMIT THEOREM - WAYAN SOMAYASA (Jurnal Matematika, 2010)
We study the construction of a version of standard Brownian sheet called h -generalized standardBrownian sheet. It is shown by means of Lindeberg’s theorem that it is a limit process of a sequence ofpartial sums processes of independent random variables in the sense of weak convergence in the metricspace of continuous functions on the compact region [0,1]×[0,1]. Based on this convergence weapproximate by simulation the quantiles of Kolmogorov, Kolmogorov-Smirnov and Cramér-von Misestype statistics which are defined as continuous functionals of the process.